Revitalizing Public Services: Addressing Challenges and Enhancing Satisfaction(A Study of Public Services in Palu City) - Mustainah Mappatoba (PT FORMOSA CENDEKIA GLOBAL, 2023)
Research on the transformation of public services, specifically e-government, is lacking in Indonesia, particularly in Palu City. Conducting this research is crucial to contribute to the field of public administration. The aim of this study is to examine the transformation of public services through e-government in Palu City, utilizing a quantitative approach. The target population includes residents of Palu City, with a focus on the One-Stop Investment Office. Data collection methods include observations, questionnaires, and documentation, while data analysis involves multiple linear regression. The findings indicate that e-government and the quality of electronic services have an impact on the satisfaction of electronic services. This highlights the importance of implementing public service transformation, encompassing e-government and e-service quality, to enhance satisfaction and mitigate unethical bureaucratic behavior, thereby providing the community with fast, convenient, and equitable services